2014
DOI: 10.1371/journal.pone.0110747
|View full text |Cite
|
Sign up to set email alerts
|

Lipidomic Assessment of Plasma and Placenta of Women with Early-Onset Preeclampsia

Abstract: IntroductionAdipose tissue is responsible for triggering chronic systemic inflammatory response and these changes may be involved in the pathophysiology of preeclampsia.ObjectiveTo characterize the lipid profile in the placenta and plasma of patients with preeclampsia.MethodologySamples were collected from placenta and plasma of 10 pregnant women with preeclampsia and 10 controls. Lipids were extracted using the Bligh–Dyer protocol and were analysed by MALDI TOF-TOF mass spectrometry.ResultsApproximately 200 l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 76 publications
3
46
1
Order By: Relevance
“…Blood plasma was the most commonly used biologic media (n = 10) (Bahado-Singh, Akolekar, Mandal, Dong, Xia, Kruger, Wishart et al 2012; De Oliveira, Câmara, Bonetti, Turco, Bertolla, Moron, Sass et al 2012; Kelly, Croteau-Chonka, Dahlin, Mirzakhani, Wu, Wan, McGeachie et al 2016; Kenny, Broadhurst, Dunn, Brown, North, McCowan, Roberts et al 2010; Kenny, Dunn, Ellis, Myers, Baker, Kell 2005; Odibo, Goetzinger, Odibo, Cahill, Macones, Nelson, Dietzen 2011; Pinto, Almeida, Martins, Duarte, Barros, Galhano, Pita et al 2015; Schott, Hahn, Kurbacher, Moka 2012; Turner, Brewster, Simpson, Walker, Fisher 2007; Turner, Brewster, Simpson, Walker, Fisher 2008), followed by serum (n = 7) (Bahado-Singh, Akolekar, Mandal, Dong, Xia, Kruger, Wishart et al 2013; Bahado-Singh, Syngelaki, Akolekar, Mandal, Bjondahl, Han, Dong et al 2015; Chen, He, Tan, Xu 2017; Kenny, Broadhurst, Brown, Dunn, Redman, Kell, Baker 2008; Koster, Vreeken, Harms, Dane, Kuc, Schielen, Hankemeier et al 2015; Kuc, Koster, Pennings, Hankemeier, Berger, Harms, Dane et al 2014), and placental or intrauterine tissue samples (n = 7) (Austdal, Thomsen, Tangerås, Skei, Mathew, Bjørge, Austgulen et al 2015; Baig, Lim, Fernandis, Wenk, Kale, Su, Biswas et al 2013; Dunn, Brown, Worton, Davies, Jones, Kell, Heazell 2012; Jain, Jayasimhulu, Clark 2004; Korkes, Sass, Moron, Câmara, Bonetti, Cerdeira, Da Silva et al 2014; Pearson, Zhang, Arya, Warren, Ortori, Fakis, Khan et al 2010; Sohlberg, Wikström, Olovsson, Lindgren, Axelsson, Mulic-Lutvica, Weis et al). The remaining studies used urine (n = 1) (Diaz, Barros, Goodfellow, Duarte, Galhano, Pita, Almeida et al 2013), urine and serum (n = 2) (Austdal, Skråstad, Gundersen, Austgulen, Iversen, Bathen 2014; Austdal, Tangerås, Skråstad, Salvesen, Austgulen, Iversen, Bathen 2015), or breast milk (n=1) (Dangat, Upadhyay, Kilari, Sharma, Kemse, Mehendale, Lalwani et al 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Blood plasma was the most commonly used biologic media (n = 10) (Bahado-Singh, Akolekar, Mandal, Dong, Xia, Kruger, Wishart et al 2012; De Oliveira, Câmara, Bonetti, Turco, Bertolla, Moron, Sass et al 2012; Kelly, Croteau-Chonka, Dahlin, Mirzakhani, Wu, Wan, McGeachie et al 2016; Kenny, Broadhurst, Dunn, Brown, North, McCowan, Roberts et al 2010; Kenny, Dunn, Ellis, Myers, Baker, Kell 2005; Odibo, Goetzinger, Odibo, Cahill, Macones, Nelson, Dietzen 2011; Pinto, Almeida, Martins, Duarte, Barros, Galhano, Pita et al 2015; Schott, Hahn, Kurbacher, Moka 2012; Turner, Brewster, Simpson, Walker, Fisher 2007; Turner, Brewster, Simpson, Walker, Fisher 2008), followed by serum (n = 7) (Bahado-Singh, Akolekar, Mandal, Dong, Xia, Kruger, Wishart et al 2013; Bahado-Singh, Syngelaki, Akolekar, Mandal, Bjondahl, Han, Dong et al 2015; Chen, He, Tan, Xu 2017; Kenny, Broadhurst, Brown, Dunn, Redman, Kell, Baker 2008; Koster, Vreeken, Harms, Dane, Kuc, Schielen, Hankemeier et al 2015; Kuc, Koster, Pennings, Hankemeier, Berger, Harms, Dane et al 2014), and placental or intrauterine tissue samples (n = 7) (Austdal, Thomsen, Tangerås, Skei, Mathew, Bjørge, Austgulen et al 2015; Baig, Lim, Fernandis, Wenk, Kale, Su, Biswas et al 2013; Dunn, Brown, Worton, Davies, Jones, Kell, Heazell 2012; Jain, Jayasimhulu, Clark 2004; Korkes, Sass, Moron, Câmara, Bonetti, Cerdeira, Da Silva et al 2014; Pearson, Zhang, Arya, Warren, Ortori, Fakis, Khan et al 2010; Sohlberg, Wikström, Olovsson, Lindgren, Axelsson, Mulic-Lutvica, Weis et al). The remaining studies used urine (n = 1) (Diaz, Barros, Goodfellow, Duarte, Galhano, Pita, Almeida et al 2013), urine and serum (n = 2) (Austdal, Skråstad, Gundersen, Austgulen, Iversen, Bathen 2014; Austdal, Tangerås, Skråstad, Salvesen, Austgulen, Iversen, Bathen 2015), or breast milk (n=1) (Dangat, Upadhyay, Kilari, Sharma, Kemse, Mehendale, Lalwani et al 2016).…”
Section: Resultsmentioning
confidence: 99%
“…An interesting approach would be to use lipidomic MS-methods to further assess the variation in lipid components in this cohort. 184 The connection between preeclampsia and CVD is re ected in all studies in this thesis. Serum pro les re ect an atherogenic lipid pro le in both early and late pregnancies where preeclampsia develops (papers I and II).…”
mentioning
confidence: 99%
“…Many authors have studied the phospholipid composition of syncytiotrophoblast cells but they did not distinguish between both membranes [4,5,45]. As syncytiotrophoblast is a polarized cell, the contribution of each phospholipid species is crucial to determine the apical or basal membrane transport function.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…It was found that the composition, structure and functions of these membrane lipid bilayers are modified with gestational progress in order to meet the metabolic needs of the growing fetus [2,3]. In addition, in pathological conditions such as preeclampsia, some authors have found alterations in membrane lipid composition of syncytiotrophoblast [4,5] and an abnormal expression of transport proteins [6][7][8][9] impairing placental functions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation